Global Semiconductor Shortage Triggering Obstructions and Production Delays - Chakraborty, Arnab (Digital Repository of Theses - SSBM Geneva, 2023)
The global COVID-19 pandemic served as an enormous shock that severely disrupted the delicate supply-demand balance in semiconductor supply chains. Lockdowns and travel restrictions temporarily halted production at overseas chip fabrication facilities. This reduced supply was misaligned with a sudden spike in semiconductor demand as consumer electronics purchases surged while working and learning from home became widespread. However, the automotive industry had drastically scaled back chip orders earlier in the pandemic as car sales plunged. This mismatch resulted in acute semiconductor shortages for automakers as production rebounded quicker than anticipated amidst chip supply rigidity. The research analyzed this complex interplay through extensive literature review, data analysis, and forecast modeling. The study synthesized perspectives from prior work examining supply chain vulnerabilities and automotive industry impacts. A thematic analysis identified key drivers including pandemic disruptions, supply-demand mismatches, manufacturing concentration risks, automotive priority gaps, and macroeconomic shifts. Financial impacts on major automakers were also reviewed. An original dataset on country-level automotive production over 22 years provided empirical insights. Descriptive analysis evidenced dramatic declines in 2020 output across all major producing economies from pandemic disruptions. China maintained production leadership despite the crisis. Sophisticated forecasting using LSTM neural networks was conducted to predict recovery timeframes and enhance preparedness. Key implications highlighted supply chain resilience strategies and collective action as imperative for managing systemic shortages. The deepening necessity and complexity of semiconductor supply chains poses risks from over-optimization without agile buffers. For the automotive industry, rethinking innovation roadmaps, increasing visibility, strategic stockpiling, and creative engineering is needed to navigate disruptions. The research limitations around constrained forecasting, conceptual materials analysis, aggregated data usage, and geographically limited literature review were acknowledged. Recommendations included addressing these gaps through expanded techniques, proprietary data access, and globally diverse information sources. Overall, the study contributed timely perspectives to aid stakeholders across electronics supply chains seeking to enhance resilience while upholding rapid innovation. The insights generated can help the automotive and semiconductor industries be better positioned to navigate future crises.